Analisis Pengaruh Lingkungan Kerja dan Pelatihan Terhadap Kinerja Karyawan - Ramadhan satrio wibowo; Mega Mirasaputri Cahyanti (Jurnal Ecogen, 2022)
Abstract : This studies start from the life of a gap in research that discusses the impact of work environment and training on employee performance. The discrepancy between the findings of the study and the existence of the phenomenon occurring in the company. The sample used in this research was 50 respondents who had a data collection method using a questionnaire. This research uses a quantitative method with non-probability sampling, and the sampling technique used is sampling jenuh / saturated sampling. The analysis used is the Frequency Test, Instrument Test by distributing questionnaires to 50 respondents. For this research, the independent variables used include training and work environment. Referring to the results of the data obtained, it is concluded that the work environment and job training variables have a significant and positive influence on employee performance.Keywords: Work environment, employee performance, employee performance.